2020
DOI: 10.1002/1348-9585.12154
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic risk exposure and work ability among young dental professionals in China: A cross-sectional study

Abstract: Background Exposure to high ergonomic risk resulted in an increasing prevalence of musculoskeletal disorders among dental professional. However, little is known about the high exposure risk impact on work ability among dental professionals. Objective We conducted a cross‐sectional study to examine the association between ergonomic risk exposure and work ability among young dental professionals in their early careers. Methods A total of 230 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
(44 reference statements)
0
6
2
1
Order By: Relevance
“… 17 , 29 Our recent investigation found that WAI reduction was significantly associated with the high level of ergonomic risk exposure. 8 Despite PE in this current study did not reach a positive effect on WAI, we still detected an improvement of WAI and this is important for young dental professionals to prevent WAI from deteriorating in their early career. The presence of a high initial work ability level among the young participants and relatively short‐term follow‐up might be the explanations.…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“… 17 , 29 Our recent investigation found that WAI reduction was significantly associated with the high level of ergonomic risk exposure. 8 Despite PE in this current study did not reach a positive effect on WAI, we still detected an improvement of WAI and this is important for young dental professionals to prevent WAI from deteriorating in their early career. The presence of a high initial work ability level among the young participants and relatively short‐term follow‐up might be the explanations.…”
Section: Discussioncontrasting
confidence: 79%
“…A RCT study showed that the participatory intervention did not reduce perceived physical workload and no evidence was found for the efficacy of the intervention in preventing musculoskeletal disorders among kitchen workers 10 . Our recent study revealed that ergonomic risk exposure was significantly associated with work ability among dental professionals 8 . It is not difficult to understand that the presence of MSDs may affect not only the physical function but also mental capacities, even future work ability prediction.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations